2017
DOI: 10.1038/s41598-017-00842-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of Wnt signaling disrupt thymus morphogenesis and function

Abstract: All vertebrates possess a thymus, whose epithelial microenvironment is essential for T cell development and maturation. Despite the importance of the thymus for cellular immune defense, many questions surrounding its morphogenesis remain unanswered. Here, we demonstrate that, in contrast to the situation in many other epithelial cell types, differentiation of thymic epithelial cells (TECs) proceeds normally in the absence of canonical Wnt signaling and the classical adhesion molecule E-cadherin. By contrast, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 77 publications
5
38
1
Order By: Relevance
“…Based on flow cytometry and TF binding site analyses, we found that PSMB11 preserved the integrity of the cTEC-specific transcriptome by inhibiting WNT signaling via degradation of b-catenin. This conclusion is consistent with the observation that constitutive WNT activation in TECs disrupts their function and skews cTECs toward an mTEC phenotype (37). The sole difference between immunoproteasomes (found in mTECs) and thymoproteasomes (present in cTECs) is the nature of their chymotryptic catalytic subunit: PSMB8 in immunoproteasomes and PSMB11 in thymoproteasomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on flow cytometry and TF binding site analyses, we found that PSMB11 preserved the integrity of the cTEC-specific transcriptome by inhibiting WNT signaling via degradation of b-catenin. This conclusion is consistent with the observation that constitutive WNT activation in TECs disrupts their function and skews cTECs toward an mTEC phenotype (37). The sole difference between immunoproteasomes (found in mTECs) and thymoproteasomes (present in cTECs) is the nature of their chymotryptic catalytic subunit: PSMB8 in immunoproteasomes and PSMB11 in thymoproteasomes.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, they strongly suggest that enhanced WNT signaling is instrumental in the acquisition of mTEC features by Psmb11 2/2 cTECs. WNT signaling is normally repressed in cTECs (in contrast to thymocytes), and upon overactivation of WNT signaling, cTECs acquire features of mTECs (36,37). The key switch in the canonical WNT pathway is the cytoplasmic protein b-catenin, whose abundance is regulated by proteasomal degradation (36).…”
Section: Psmb11 Is Necessary To Repress Wnt Signaling In Ctecsmentioning
confidence: 99%
“…However, recent results indicate that a proper thymus development can only occur when β-catenin-dependent Wnt signaling is low or lacking [133]. Thus, β-catenin-deficient thymi exhibit Foxn1 expression, and stabilized β-catenin overexpression shows decreased rather than increased Foxn1 transcripts [133,134]. Therefore, these results suggest that β-catenin is dispensable for Foxn1 expression in fetal TECs.…”
Section: Wnt Familymentioning
confidence: 87%
“…Thus, overexpression of Dkk1, a Wnt4 inhibitor, in TECs induces thymic atrophy with reduced epithelial progenitors and TEC proliferation and appearance of TEC proliferation [132]. However, recent results indicate that a proper thymus development can only occur when β-catenin-dependent Wnt signaling is low or lacking [133]. Thus, β-catenin-deficient thymi exhibit Foxn1 expression, and stabilized β-catenin overexpression shows decreased rather than increased Foxn1 transcripts [133,134].…”
Section: Wnt Familymentioning
confidence: 99%
See 1 more Smart Citation